2007
DOI: 10.1175/jpo3004.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Spinup of the South Pacific Subtropical Gyre

Abstract: An increase in the circulation of the South Pacific Ocean subtropical gyre, extending from the sea surface to middepth, is observed over 12 years. Datasets used to quantify the decadal gyre spinup include satellite altimetric height, the World Ocean Circulation Experiment (WOCE) hydrographic and float survey of the South Pacific, a repeated hydrographic transect along 170°W, and profiling float data from the global Argo array. The signal in sea surface height is a 12-cm increase between 1993 and 2004, on large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
241
1
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(282 citation statements)
references
References 23 publications
34
241
1
6
Order By: Relevance
“…They map qualitatively onto the schematic of the observed temperature and salinity changes across a meridional section of the Southern Ocean, with warmer, saltier, and older waters south of the polar front and cooler, fresher, and younger waters north of the polar front (5,23). Further, they are consistent with the observed intensification of the southern subtropical gyres (24), increases in dissolved oxygen in the subtropical Indian Ocean and decreases in dissolved oxygen in the polar Southern Ocean (25,26), and a slowdown of carbon uptake in Antarctic waters in recent decades (2) because of enhanced upwelling of polar CDW, which brings old carbon-rich deep waters to the surface.…”
supporting
confidence: 59%
“…They map qualitatively onto the schematic of the observed temperature and salinity changes across a meridional section of the Southern Ocean, with warmer, saltier, and older waters south of the polar front and cooler, fresher, and younger waters north of the polar front (5,23). Further, they are consistent with the observed intensification of the southern subtropical gyres (24), increases in dissolved oxygen in the subtropical Indian Ocean and decreases in dissolved oxygen in the polar Southern Ocean (25,26), and a slowdown of carbon uptake in Antarctic waters in recent decades (2) because of enhanced upwelling of polar CDW, which brings old carbon-rich deep waters to the surface.…”
supporting
confidence: 59%
“…The authors argued that the sea level signature in the equatorial Pacific associated with the SAM may partly reflect ENSO influence on the SAM, as suggested by existing studies (e.g., Ding et al 2012). Roemmich et al (2007) suggested that the decadal spin up of the Subtropical Gyre over the South Pacific, which is associated with a 12-cm increase in satellite-observed SSH between 1993 and 2004 on large spatial scales centered at about (40°S, 170°W), results from the increased surface wind stress curl associated with an enhanced SAM. Regression analyses using a longer record of 1958-2007, however, do not show a strong influence of SAM in the South Pacific Subtropical Gyre region (Fig.…”
Section: The Southern Oceanmentioning
confidence: 86%
“…Previous studies suggest that over the past few decades change in wind forcing is the main cause for decadal sea level variability in the Pacific, including the intensified SLR in the western tropical Pacific since the early 1990s (e.g., Qiu 2002;Carton et al 2005;Bindoff et al 2007;Köhl et al 2007;Köhl and Stammer 2008;Roemmich et al 2007;Timmermann et al 2010;Merrifield and Maltrud 2011;McGregor et al 2012;Nidheesh et al 2013;Qiu and Chen 2012;Han et al 2014a). Given that a significant portion of the basinscale coherent sea level pattern is associated with the PDO and NPGO, one can conclude that it is the surface wind changes associated with the PDO and NPGO that are the major cause for the basin-wide sea level patterns.…”
Section: Forcing and Processesmentioning
confidence: 99%
“…Previously, the strengthening WBCs has been documented individually, for example, the Gulf Stream (Curry and McCartney, 2001), Kuroshio Current (Qiu and Joyce, 1992;Deser et al, 1999;Sato et al, 2006;Sakamoto et al, 2005) and the Eastern Australia Current (Cai et al, 2005;Qiu and Chen, 2006;Ridgway, 2007;Roemmich et al, 2007;Ridgway et al, 2008). Curry andMcCartney (2001) found that transport of the Gulf Stream has intensified after the 1960s.…”
Section: Discussionmentioning
confidence: 99%